Long-run projection of the Japanese economy: a critical evaluation - Kitamura, Hiroshi (1956)
The author is a member of the Japanese Government's Advisory Council on Economic Affairs. This article has been written during his stay at the Center for International Studies, Massachusetts Institute of Technology, as joint guest of the Center and the Department of Economics. The article draws heavily on the materials prepared by the experts of the Economic Planning Board, but opinions and judgments are presented solely on the author's own responsibility and do not reflect in any sense those of the Council nor the Economic Planning Board. The author is indebted to George B. Baldwin for editorial help as well as for many valuable suggestions.
It's a photocopy of the original
Keywords: Economy -- Japan